Detection of Pesticide Residues (Imidacloprid, Aldicarb, Metalaxyl, Cypermethrin, Chlorpyrifos, DDA, and Endrin) in Peach Samples Collected from Jabal al Akhdar farms, Libya - Salah Hasan; Omukthum Abduljalil; Fatma Mohamed; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was conducted to determine the presence of pesticide residues, specifically (Imidacloprid, Aldicarb, metalaxl, cypermethrin, chlorpyrifos, DDA, and Endrin) in peach samples collected from various regions in eastern Libya, including (Qarnadah, Iqafnata, Abdul Wahid, Qasr Libya, and Al-Marj). The analytical methodology employed a (UV-Vis) spectrophotometer in conjunction with the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) extraction technique for the estimation of pesticide concentrations in the peach specimens. The quantitative detection limits of the (UV-Vis) spectrophotometer for standard pesticide solutions were determined as follows: cypermethrin (0.52, 1.58 µg/ml), chlorpyrifos (0.53, 1.61 µg/ml), Imidacloprid (0.64, 1.95 µg/ml), metalaxll (0.27, 8.32 µg/ml), Aldicarb (0.90, 2.73 µg/ml), DDA (3.50, 10.62 µg/ml), and Endrin (1.89, 5.73 µg/ml). The findings revealed detectable residues of (cypermethrin and Imidacloprid) exclusively in samples from the Al-Marj region, according to the instrument’s limit of detection (LOD). The detected concentrations were below the maximum residue limits established by the European Union (0.860 µg/ml).